Semaglutide and Cardiovascular Outcomes in Obesity without Diabetes - Lincoff, A. Michael; Brown-Frandsen, Kirstine; Colhoun, Helen M.; Deanfield, John; Emerson, Scott S.; Esbjerg, Sille; Hardt-Lindberg, Søren; Hovingh, G. Kees; Kahn, Steven E.; Kushner, Robert F.; Lingvay, Ildiko; Oral, Tugce K.; et al. (The New England journal of medicine, 2023)
In a trial in patients with cardiovascular disease and overweight or obesity but no diabetes, semaglutide was superior to placebo in lowering the risk of major adverse cardiovascular events at a mean follow-up of 39.8 months.